HUBUNGAN POLA ASUH ORANG TUA DENGAN MOTIVASI BELAJAR SISWA DI MTs RAUDLATUL ULUM BLUTO - ragil armadhani; rusmiyati rusmiyati; khoirul asiah; choli astutik (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2022)
Parenting style is one of the best ways parents can take in educating children as an embodiment of a sense of responsibility to children. This attitude is refelected in certain paenting patterns. Social status is an extreme factor in the subject of learning., has an important role in the development of children in the family. . Learning motivation must be instilled in children early on. Someone who has strong motivation will have a lot energy in learning. In this study using quantitative engineering reseacrh with correlational types which uses findings regarding data obtained in the field is processed using SPSS version 16.0 for windows. Keywords : Parenting motivation, Learning motivation, Correlational